Why conspiracy theories matter: A social psychological analysis. (1st January 2018) - Douglas, Karen M.; Sutton, Robbie M.
ABSTRACT: Although conspiracy theories have arguably always been an important feature of social life, they have only attracted the attention of social psychologists in recent years. The last decade, however, has seen an increase in social psychological research on this topic that has yielded many insights into the causes and consequences of conspiracy thinking. In this article, we draw on examples from our own programme of research to highlight how the methods and concepts of social psychology can be brought to bear on the study of conspiracy theories. Specifically, we highlight how basic social cognitive processes such as pattern perception, projection and agency detection predict the extent to which people believe in conspiracy theories. We then highlight the role of motivations such as the need for uniqueness, and the motivation to justify the system, in predicting the extent to which people adopt conspiracy explanations. We next discuss how conspiracy theories have important consequences for social life, such as decreasing engagement with politics and influencing people's health and environmental decisions. Finally, we reflect on some of the limitations of research in this domain and consider some important avenues for future research.